Trabalho, ambiente e saúde: cotidiano dos fazeres da mulher rural na Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
This research identifies, characterizes and analyses the dimensions of work, health and environment of agriculturist women from Sagrado Coração de Jesus/Vila do Engenho community located in the city of Itacoatiara, Amazonas. The goal is to identify different places, processes and organizations regarding the work of women, in its multiple activities, that are incorporated, in the day-to-day help, and also to identify health risks referenced by the worker in the day-to-day work. This qualitative research through the theorical criticism perspective in the sociohistorical approach, dialogues with the psychodynamics of work theories. These theories opt for the speech and listening as privileged access to subjective experiences. In order to understand the work of women in the agriculture, it is important to trace an access between its geographical, psychosocial and health aspects. This research uses the Nucleus of Meaning Analysis (NMA), inspired and adapted from the Category-based Content Analysis, that privileges the words, the subjective experiences analysis and the studies of their meanings. The results show that in Vila do Engenho, histories are connected to the cooperative dynamic with the protagonism of women at work experiences, in the organization and participation in the community. Contradictions and current conditions in which they live, through their own reflection as people, and through the action of the subject that tends to transform material conditions that generated such contradictions, constitute the work dynamic in which they live. As results, it can be confirmed that through their histories, work is determining in the health/disease process of the agriculturist women, in which working is to make a work-help relation. It is possible to observe that for these women, it is not so clear of which function performed daily can be identified as help and work. The role of the woman as a mere helper disappears when the relations of work become complex. On the other hand, when these relations are less complex, the idea of helping the husband is better considered. It is revealed an invisible work that extrapolates "housewifing". There are situations and places that increase the level of exploration of this work force, house - association - agro-industry - plantation, associated by the woman as much as their proper duties. In the agriculture work, it can be observed that the women acquire pain due to bad posture, physical effort and to mechanical pression on determined body parts, like the lower and the upper limbs, heat and solar radiation exposure for long periods of time and agrochemicals exposure, and also the ones related to organization and psychosocial factors of each job, associated to common work overload in all places of Vila. The public space permits the speech, that can be heard and demands actions, favoring women to question the place they are given, and the strenghtening of the worker identity, inserted in the reproductive and productive spaces of agriculture in the rural environment of the Amazon.
Keywords: Processo e organização do trabalho; Saúde do trabalhador rural; Rural work; Process and organization of Work; Rural workers' health; OUTROS